Intelligent service restoration in smart distribution network - Zakaria, Zuhaina (Penerbit UiTM (UiTM Press), 2025)
This book explores how intelligent techniques can enhance the performance and reliability of modern power distribution systems. With the increasing complexity of distribution networks driven by renewable integration, evolving load demands, and digitalisation, it addresses key challenges in restoring service quickly and efficiently when faults occur. The book presents methods for intelligent service restoration in smart distribution networks, offering practical solutions for improving reliability and operational efficiency.